2008
DOI: 10.1120/jacmp.v9i4.2828
|View full text |Cite
|
Sign up to set email alerts
|

Simulation of intrafraction motion and overall geometric accuracy of a frameless intracranial radiosurgery process

Abstract: We conducted a comprehensive evaluation of the clinical accuracy of an image‐guided frameless intracranial radiosurgery system. All links in the process chain were tested. Using healthy volunteers, we evaluated a novel method to prospectively quantify the range of target motion for optimal determination of the planning target volume (PTV) margin. The overall system isocentric accuracy was tested using a rigid anthropomorphic phantom containing a hidden target. Intrafraction motion was simulated in 5 healthy vo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
18
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(18 citation statements)
references
References 43 publications
0
18
0
Order By: Relevance
“…Several studies compared these two systems and concluded they had similar accuracy (6,7) . These advances considerably increased the setup precision, and allowed the use of different types of frameless masks with a comparable accuracy to that of the invasive frame approach (8‐13) …”
Section: Introductionmentioning
confidence: 99%
“…Several studies compared these two systems and concluded they had similar accuracy (6,7) . These advances considerably increased the setup precision, and allowed the use of different types of frameless masks with a comparable accuracy to that of the invasive frame approach (8‐13) …”
Section: Introductionmentioning
confidence: 99%
“…The accuracy and precision of frameless mask systems for inter‐ and intrafraction motion has been studied extensively in humans but there is limited information regarding their use in veterinary medicine . In a comparison study of frame‐based versus frameless systems using Brainlab equipment, the setup accuracy of the frameless system was shown to be comparable to the frame‐based system .…”
Section: Introductionmentioning
confidence: 99%
“…( 4 ) The geometric accuracy of the 6D robotic couch system has been studied previously and it was found that the overall system accuracy was around 0.31±0.77 mm range. ( 5 , 6 ) Intrafraction setup variability by X‐ray system for hypofractionated cranial and body radiotherapy has been investigated, and the motion range for abdomen was 1.3±1.2 mm ( 7 ) and 1.19±0.45 mm for the frame‐based technique. ( 8 )…”
Section: Introductionmentioning
confidence: 99%